2016
DOI: 10.1038/mi.2015.81
|View full text |Cite
|
Sign up to set email alerts
|

Social stress-enhanced severity of Citrobacter rodentium-induced colitis is CCL2-dependent and attenuated by probiotic Lactobacillus reuteri

Abstract: Psychological stressors are known to affect colonic diseases but the mechanisms by which this occurs, and whether probiotics can prevent stressor effects, are not understood. Because inflammatory monocytes that traffic into the colon can exacerbate colitis, we tested whether CCL2, a chemokine involved in monocyte recruitment, was necessary for stressor-induced exacerbation of infectious colitis. Mice were exposed to a social disruption stressor that entails repeated social defeat. During stressor exposure, mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
41
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 49 publications
4
41
1
Order By: Relevance
“…We have previously demonstrated that stressor-induced increases in C. rodentium levels are associated with increases in C. rodentium -induced colonic pathology, and that L. reuteri can attenuate the effects of the stressor on colonic pathology18. Thus, markers of colonic inflammation were assessed to verify that the L. reuteri attenuated the effects of the stressor in the current study.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…We have previously demonstrated that stressor-induced increases in C. rodentium levels are associated with increases in C. rodentium -induced colonic pathology, and that L. reuteri can attenuate the effects of the stressor on colonic pathology18. Thus, markers of colonic inflammation were assessed to verify that the L. reuteri attenuated the effects of the stressor in the current study.…”
Section: Resultsmentioning
confidence: 80%
“…Thus, markers of colonic inflammation were assessed to verify that the L. reuteri attenuated the effects of the stressor in the current study. We previously found that colon mass strongly correlates with colonic histopathology18. Thus, we assessed colon mass as a surrogate marker of colonic pathology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, like studies in rats (Reber et al, 2006; Reber et al, 2008; Veenema et al, 2008), exposure to stress enhances the response to inflammatory challenge in the colon. For example, we have shown that exposing mice to either the prolonged restraint stressor or to the SDR stressor significantly increases the inflammatory response to the colonic pathogen Citrobacter rodentium (Mackos et al, 2013; Mackos et al, 2016). This excessive inflammatory response is associated with immunopathology in the colon, and is consistent with clinical studies indicating that the symptoms of colonic diseases, such as the inflammatory bowel diseases, tend to be more severe during stressful periods.…”
Section: Detrimental Effects Of the Microbiota On Host Immunity Durinmentioning
confidence: 99%
“…This led to a series of experiments in which mice were given probiotic lactobacilli to determine whether increasing Lactobacillus levels in the intestines would prevent the deleterious effects of the stressor on colonic inflammation. Administering probiotic Lactobacillus reuteri (ATCC23272) was shown to restore barrier function in outbred CD-1 mice exposed to the restraint stressor during C. rodentium challenge (Mackos et al, 2013), and prevented the exacerbating effects of the SDR stressor on colonic immunopathology in inbred C57BL/6 mice challenged with C. rodentium (Mackos et al, 2016). When considered together, these studies demonstrate that stressor exposure changes the composition of the microbiota and that microbes are involved with stressor-induced changes in mucosal and systemic immune responses.…”
Section: Detrimental Effects Of the Microbiota On Host Immunity Durinmentioning
confidence: 99%